Green logistics performance and infrastructure on service trade and environment-Measuring firm’s performance and service quality - Yingfei, Yang; Mengze, Zhang; Zeyu, Lin; Ki-Hyung, Bae; Andriandafiarisoa Ralison Ny Avotra, Andrianarivo; Nawaz, Ahsan (Journal of King Saud University. Science, 2022)
The link between infrastructure and green logistics performance in the services sector has been studied in this study. The mediating function of business performance and service quality are also discussed in this study as this is a deductive and cross-sectional study, the hypothesis was first formulated based on the literature gap and then tested. The unit of analysis is management personnel, entry-level economists, and financial analysts. The structural equation modeling-partial least-squares analysis (PLS-SEM) approach was employed in this investigation. The authors validated the reliability and validity of constructs and indicators used to measure constructs by assessing measurement models. The measurement methodology has then utilized to confirm the study hypothesis. The study results demonstrate that infrastructure and green logistics performance have a beneficial influence on services trade and environment; besides that, service quality and company performance are also important factors in improving services trade in China. Furthermore, firm performance and service quality have been identified as strong positive mediators between Green logistic performance, infrastructure, and services trade & environment. This study has a theoretical contribution by introducing, verifying, and proposing a new measurement for three variables: infrastructure, green logistic performance, and services trade & environment. This study has numerous relevant and helpful implications for government agencies and departments. It will provide a pathway for the upcoming industry practitioners in terms of green logistic performance and service trade & environment.